La seguridad industrial: plan integral para la prevención del riesgo laboral en la empresa AMSUL de la ciudad de Machala. - Cuenca León, Gilma Del Carmen (2017)
The purpose of this thesis is to ensure that the company Amsul has a timely and efficient response to a casualty emergency and is not affected by the changes and difficulties that put them at risk of disappearing when these situations arise, if we develop managerial skills in The work team both administrative and labor, have the vision that allows their support and their competitive position in the market because you only think about the present and do not see necessary to invest in development or modifications to keep the business going well. For the company Amsul is essential to find scenarios that allow it to successfully face the challenges of growth, survival and technology in its daily processes, in addition to working with customers and suppliers otherwise runs the risk of disappearing this entity. The Company provides technical service of maintenance of recharge of fire extinguishers, networks against fires and also industrial safety equipment to the different industries; The main objective is to develop a comprehensive plan for the prevention of occupational risk in the company Amsul. Methods of data collection surveys, interviews, observation, statistics allowed us to identify the current problem. From the results obtained, the proposal for a comprehensive plan that reduces and foresees the occupational risk and achieve a safe environment in the Amsul Company is structured.